Modeling particle-particle binary coagulation rate constants for spherical aerosol particles at high volume fractions using Langevin Dynamics simulations. (August 2022) - Suresh, Vikram; Liu, Zhibo; Perry, Zachary; Gopalakrishnan, Ranganathan
Abstract: Effect of volume-fraction and particle-particle hydrodynamic interactions on the coagulation rate of particles are investigated. Particle coagulation is modeled using Langevin Dynamics (LD) based trajectory simulations of N mono-sized spherical particles in a periodic domain. The extended Kirkwood-Risemann approach (J. Fluid Mechanics 855, 535 (2018)) is invoked to compute particle-particle hydrodynamic interactions whose effect is parameterized as a function of the momentum Knudsen number ( K n ). The results are summarized as a model for coagulation rate constant ( β i j ) that depends on the diffusive Knudsen number ( K n D ) used in prior work to parameterize coagulation in the dilute regime (Aerosol Sci. Tech. 45, 1499 (2011)), K n and particle volume-fraction η v . In the absence of hydrodynamic interactions, it is observed that the coagulation rate constant in the continuum limit for mass transfer ( K n D → 0 ) is significantly enhanced by a factor of ∼80 at η v ∼ 0.3 due to particle crowding. While considering hydrodynamic interactions for η v ≥ 0.05, we use a screening distance around each particle that scales inversely with η v beyond which the contribution of farther neighbors is neglected owing to the rapid decay of hydrodynamic interactions with distance. We also present new LD calculations of β i j and elucidate the dependence of the same on K n 1 and the particle radii ratio θ r for the coagulation of two particles in the dilute limit η v → 0 . It is observed that the reduction of β i j becomes significant as K n 1 → 0 : at the lowest momentum Knudsen number considered ( K n 1 = 0.1 ): β i j is reduced by a factor of ∼10 for equally sized particles ( θ r = 0.5 ) . At high K n D, K n 1, the particle size disparity is not significant, and it is seen that β i j matches hard sphere predictions, indicating the insignificant contributions by hydrodynamic interactions. A series of animations of 2-particle simulations are presented as part of the Supplemental Information to illustrate the role of hydrodynamic interactions in particle coagulation. Computational results are summarized as regressions for convenient incorporation into particle/droplet growth sectional models. Highlights: Particle coagulation at high volume fraction is examined using Langevin Dynamics. At high volume fraction, coagulation rate constant is enhanced significantly. Hydrodynamic interactions decrease the increase in coagulation rate constant. Effect of particle radius is examined in the dilute limit. A regression-based coagulation rate constant model is presented for usage.